Students' Perceptions of the Concept of Halal Tourism at Bira White Sand Beach - Irwan Irwan; Adi Sumandiyar (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research explores students' perceptions of halal tourism at Pasir Putih Bira Beach, Bulukumba Regency, and their potential in promoting halal tourism based on local culture. The research uses a qualitative approach with a case study design. The informants were 50 high school students in classes XI and XII, selected based on religiosity, domicile near tourist areas, and travel experience. Data collection techniques include in-depth interviews, participant observation, and documentation. The research results show that most students have a normative understanding of halal tourism, such as the importance of worship facilities, halal food, and restrictions on interactions between genders. However, gaps were found between this understanding and the reality on the ground, including the lack of halal facilities and tourist behavior that was not in line with religious values. Students experience a dilemma between maintaining religious values ​​and the reality of modern tourism. The research conclusion shows that students have the potential to become halal tourism promotion agents by integrating local cultural values ​​such as politeness and respect for guests. This research recommends educating the younger generation and promoting halal tourism based on local wisdom to create inclusive and competitive destinations.